PENTINGNYA PERAN GURU DALAM PENDIDIKAN INKLUSIF DI SEKOLAH DASAR - Surfilda Dwi Atika; Nova Estu Harsiwi (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
Education for children with special needs is something that the Indonesian government must pay close attention to. This research aims to understand the teacher's role in inclusive education in elementary schools. The research method used is descriptive qualitative. The sampling method used in this study is purposive sampling, which selects teachers of classes that include children with special needs. Data was collected using in-depth interview techniques with the fourth-grade teachers at SDN Tanah Kali Kedinding 1. The research results show that teachers play an important role in the success of inclusive education for children with special needs.